Management options for the walnut twig beetle, Pityophthorus juglandis blackman, vector of the fungal canker pathogen Geosmithia morbida - Sitz, Rachael, author; Cranshaw, Whitney, advisor; Tisserat, Ned, advisor; Jacobi, William, committee member; Klett, James, committee member (Colorado State University. Libraries, 2013)
The walnut twig beetle, Pityophthorus juglandis (Blackman) and its fungal associate Geosmithia morbida have recently been discovered to produce thousand cankers disease. Pityophthorus juglandis is native to the southwestern United States, but its geographic range is expanding, as is incidence of thousand cankers. The disease occurs in multiple walnut species, but it has devastated black walnut (Juglans nigra) populations in several western states. To better understand and manage thousand cankers disease, studies were initiated to (1) determine monthly variations in P. juglandis cold tolerance, (2) develop effective management tools for infested felled logs, and (3) determine suitable fungicides to treat thousand canker diseased trees and techniques to create Geosmithia-free beetle populations. Monthly variations in cold tolerance were measured by the supercooling point (SCP) to predict the survival of P. juglandis within the native range of black walnut. Mean SCPs were the highest for larvae (-14.2°C) in the month of September and lowest for adults in October (19.7°C). These studies, as well as beetle survival in infested Colorado trees where temperatures reached -29°C in February 2011, suggest P. juglandis could survive the winter in much of the native range of black walnut, but may be limited in trees where temperatures regularly exceed the lower lethal temperatures. Finding effective management options for thousand cankers disease is critical to decrease further expansion into urban and eastern walnut forests by the movement of infested walnut wood. In a series of experiments, we tested the effect of insecticide, temperature, submergence, and chipping treatments on P. juglandis. Insecticidal treatments were more than 80 percent effective. Heat treatments of 60°C for 30 minutes and cold treatments of -25°C for seven days were effective phytosanitary methods to control P. juglandis. Although temperature treatments eliminated P. juglandis populations, re-colonization occurred if logs were exposed to beetles. Soaking logs for eight days in 70% ethanol sanitized logs, but P. juglandis survived water soaks. Chipping infested material was over 90 percent effective, and emergence from chipped material ceased after two weeks. These experiments provide baseline management options for walnut logs infested with P. juglandis, and show the importance of properly storing treated logs to prevent re-colonization. Suitable fungicides were determined for their ability to inhibit or kill in-vitro Geosmithia morbida colonies. In an attempt to obtain sterile beetles, fungicide, bleach, and ethanol rinses were tested. Ten µg/g of thiophanate-methyl (active ingredient in Cleary's 3336F) inhibited G. morbida growth by 20%, but the fungus was inhibited by greater than 97 percent in potato dextrose agar amended with 10 µg/g or higher concentrations of the fungicide azoxystrobin (active ingredient in the fungicide Heritage). In contrast the fungus was completely inhibited and killed in agar amended with 0.6 µg/g azoxystrobin and 1.0 µg/g propiconazole (active ingredients in the fungicide Headway) along with 6.4 µg/g of propiconazole (active ingredient in the fungicide Banner MAXX). Using a first order decay regression model, the effective concentrations needed to decrease G. morbida mycelial growth by 50 percent and 90 percent (EC50 and EC90 respectively) were determined for the active ingredients azoxystrobin and/or propiconazole. The combination of sterilizing agents used in this experiment did not effectively disinfest P. juglandis adults or larvae of G. morbida.
Keywords: cold tolerance; Geosmithia; heat treatment; management; thousand cankers disease; walnut twig beetle